Science and technology in islam : catalogue of the exhibition of the Institute for the History of Arabic-Islamic Science (Johann Wolfgang Goethe University in Frankfurt, Germany) at the Frankfurt Book Fair 2004 = Wissenschaft und technik im islam : katalog der ausstellung des Instituts für Geschichte der Arabisch-Islamischen Wissenschaften (J. W. Goethe Universität, Frankfurt) anlässlich der Frankfurter Buchmesse, 6.-10. Oktober 2004. - Sezgin, Fuat, 1924-2018. (Frankfurt am Main)
76, [4] s.